Epidemiology of primary systemic vasculitis in children: a population-based study from southern Sweden. (4th July 2018) - Mossberg, M; Segelmark, M; Kahn, R; Englund, M; Mohammad, AJ
Abstract : Objectives : To estimate the annual incidence rate of paediatric primary systemic vasculitis (PSV) in a defined geographical area in southern Sweden. Methods : Potential cases of PSV [IgA vasculitis (IgAV, Henoch–Schönlein purpura), Kawasaki disease (KD), granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), eosinophilic granulomatosis with polyangiitis (EGPA), polyarteritis nodosa (PAN), and Takayasu's arteritis (TAK)] were identified in a comprehensive regional healthcare register. The study area is Skåne, the southernmost county of Sweden (population 1.29 million; 21.4% aged <18 years). Case records for children (0–17 years) assigned a diagnosis code between M300 and M319 and/or D690 were reviewed to ascertain diagnosis. Only patients diagnosed between 2004 and 2014 were included. Results : In total, 556 patients with PSV were identified. The annual incidence rate per million children (95% confidence interval) was estimated to be 200 (183–217) for all PSV, 175.5 for IgAV (160–191), 20.1 for KD (14.9–25.4), 1.4 (0–2.8) for each of GPA and MPA, 0.7 (0–1.7) for PAN, and 0.4 (0–1.1) for each of EGPA and TAK. Among children aged <10 years, 99.5% of cases were either IgAV or KD, both exhibiting a seasonal pattern paralleling infections. There were no deaths, but three cases of end-stage renal disease were noted, all in MPA. Conclusions : Vasculitis is relatively common during childhood. Mild cases associated with the infection season are most common in the youngest age groups, while during adolescence a substantial proportion has more severe forms of vasculitis.